Branding of Human Resource Technologies - How far Indian corporations could do it? - Barman , Arup (Gyan Management Journal, 2013)
Innovation and branding of HR technology is becoming vital for corporate human resource management. Branding of HR-technologies are result of adoption of innovative practice of HRM and management business sustainability. Due to turbulent competition, ongoing attempt to respond to such competition by the corporations and HR practitioners are thinking of branding their innovative techniques. In many cases, professionals are thinking about patenting of such techniques. HR innovations and branding aspects are slowly drawing attention among the corporations in India but 'How much the Indian corporations are in progress of HR innovation?' is a serious question? The present paper attempts to h(ghlight on the process of innovations and branding of human resource technologies. In addition, author appraised the extent, scope, and future perfect of branding HRTechniques in thecontextofindia.
Keywords: Branding; Resource Strength; lnnovation; Adoption